A novel Ca2+ current blocker promotes angiogenesis and cardiac healing after experimental myocardial infarction in mice. (August 2018) - Cui, Guozhen; Xin, Qiqi; Tseng, Hisa Hui Ling; Hoi, Maggie PuiMan; Wang, Yan; Yang, Binrui; Choi, InLeng; Wang, Yuqiang; Yuan, Rong; Chen, Keji; Cong, Weihong; Lee, Simon MingYuen
Graphical abstract: Abstract: We previously reported a novel danshensu derivative (R)-(3, 5, 6-Trimethylpyrazinyl) methyl-2-acetoxy-3-(3, 4-diacetoxyphenyl) propanoate (ADTM) that exhibited promising cardiovascular protective activities, such as antioxidant and antiplatelet activities, as well as arterial relaxation. Particularly, ADTM treatment for 24 h exhibited anti-oxidative activity and effectively protected against acute myocardial infarction (MI) in a rat model. Here, we further investigated the pharmacological actions of 14 days of treatment with ADTM in alleviating and restoring the MI size by stimulating revascularization. The pro-angiogenesis activity of ADTM has been validated in multiple experimental models including MI mouse, zebrafish, human umbilical vein endothelial cells (HUVECs) and A7r5 vascular smooth muscle cells (VSMCs). In addition, the effect of ADTM on L-type Ca 2 + current ( I CaL ) was determined. We demonstrated that ADTM (12–24 mg/kg) treatment for 14 days significantly decreased myocardial infarct size, increased the blood vessel density compared to vehicle in the myocardial peri-infarct area, and ADTM (24 mg/kg) enhanced the serum VEGF level in MI mice ( P < 0.05). We also demonstrated that treatment with ADTM at 50–200 μM rescued chemical-induced blood vessel loss in zebrafish. Although ADTM did not directly promote the features of angiogenesis in HUVECs, ADTM significantly increased VEGF production in a dose-dependent manner in A7r5 cells ( P < 0.05). A patch clamp experiment demonstrated that ADTM (200 μM) inhibited I CaL at all depolarizing voltages, with > 50% inhibition at + 10 mV. Taken together, our results indicated that ADTM served as a Ca 2+ current blocker, promoted angiogenesis and reduced experimental myocardial infarct size in mice, probably through stimulation of VEGF production in VSMCs.